A Qualitative Inquiry Into the Impact of the Hong Kong LPATE Over the Past Decade and a Half: Changes, Challenges, and Implications. Issue 1 (1st January 2019) - Coniam, David; Falvey, Peter; Xiao, Yangyu
ABSTRACT: Over the past two decades awareness has been growing that English language teachers need good English language proficiency and professional training to teach effectively. To address this issue, a benchmark—minimum standards assessment test—was initiated, developed, and introduced in Hong Kong in 2001. Because more than a decade and a half has now elapsed since the introduction of the LPATE, the current study explores some of the changes and challenges that have emerged since the introduction of this minimum standards language test for English language teachers. Using a qualitative approach, the study collected interview responses from 24 participants in primary and secondary schools in Hong Kong. Results indicate that changes were generally perceived positively, with English language teachers becoming better trained, with an enhanced awareness of professionalism in the profession, and English teacher standards becoming guaranteed through the implementation of the LPATE. Although the LPATE was not without its attendant controversies, 15 years later, respondents generally view the test as having fulfilled its mission and consequently now somewhat limited.